Bioequivalence assessment of high-capacity polymeric micelle nanoformulation of paclitaxel and Abraxane® in rodent and non-human primate models using a stable isotope tracer assay. (November 2021) - Hwang, Duhyeong; Vinod, Natasha; Skoczen, Sarah L.; Ramsey, Jacob D.; Snapp, Kelsie S.; Montgomery, Stephanie A.; Wang, Mengzhe; Lim, Chaemin; Frank, Jonathan E.; Sokolsky-Papkov, Marina; Li, Zibo; Yuan, Hong; et al.
Abstract: The in vivo fate of nanoformulated drugs is governed by the physicochemical properties of the drug and the functionality of nanocarriers. Nanoformulations such as polymeric micelles, which physically encapsulate poorly soluble drugs, release their payload into the bloodstream during systemic circulation. This results in three distinct fractions of the drug-nanomedicine: encapsulated, protein-bound, and free drug. Having a thorough understanding of the pharmacokinetic (PK) profiles of each fraction is essential to elucidate mechanisms of nanomedicine-driven changes in drug exposure and PK/PD relationships pharmacodynamic activity. Here, we present a comprehensive preclinical assessment of the poly (2-oxazoline)-based polymeric micelle of paclitaxel (PTX) (POXOL hl -PM), including bioequivalence comparison to the clinically approved paclitaxel nanomedicine, Abraxane®. Physicochemical characterization and toxicity analysis of POXOL hl -PM was conducted using standardized protocols by the Nanotechnology Characterization Laboratory (NCL). The bioequivalence of POXOL hl -PM to Abraxane® was evaluated in rats and rhesus macaques using the NCL's established stable isotope tracer ultrafiltration assay (SITUA) to delineate the plasma PK of each PTX fraction. The SITUA study revealed that POXOL hl -PM and Abraxane® had comparable PK profiles not only for total PTX but also for the distinct drug fractions, suggesting bioequivalence in given animal models. The comprehensive preclinical evaluation of POXOL hl -PM in this study showcases a series of widely applicable standardized studies by NCL for assessing nanoformulations prior to clinical investigation. Graphical abstract: Image 1